Romania : Request for a Stand-By Arrangement. (IMF Staff Country Reports; Country Report ;, 2001)
Romania showed progress in stabilization and reform, facilitated by substantial fiscal and external adjustments, under the Stand-By Arrangement. Executive Directors commended these developments, and emphasized the need to improve fiscal and monetary policies, and accelerate structural reforms. Directors appreciated the authorities' commitment to accelerate European Union accession, and stressed the need for fiscal consolidation, financial discipline in state-owned enterprises, and rapid privatization for reducing inflation and protecting external sustainability. They urged the authorities for the full implementation of the economic program, and approved a Stand-By Arrangement.